(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Barpy Akyn is recognized as a poet who continued his work in two eras, living before the revolution and during the Soviet era. In the pre-revolutionary period, he mingled with the public and sang his songs orally. During the Soviet era, his songs were published in newspapers and magazines. Along with Ala-Too, Baichechekey, Kyrchyn magazines almost all of the poet’s poems were published with poems related to the Communist Party, the October Revolution, 1917, Lenin, and love lyrics for children. In addition, many poets and writers wrote articles about Barpy. The article provides information about which poems of the poet Barpy were published in the Kyrgyz press, especially in cultural journals, during the Soviet period.